Detailed mutational analysis of Vga(A) interdomain linker: implication for antibiotic resistance specificity and mechanism - Lenart, Jakub; Vimberg, Vladimir; Vesela, Ludmila; Janata, Jiri; Balikova Novotna, Gabriela (Antimicrobial agents and chemotherapy, 2015)
Detailed mutational analysis examines the roles of individual residues of the Vga(A) linker in determining the antibiotic resistance phenotype. It defines a narrowed region of residues 212 to 220 whose composition determines the resistance specificity to lincosamides, pleuromutilins, and/or streptogramins A. From the analogy with the recently described function of the homologous ABC-F protein EttA as a translational factor, we infer that the Vga(A) linker interacts with the ribosome and directly or indirectly affects the binding of the respective antibiotic.
Keywords: ribozomy; streptograminy; Drug Resistance, Multiple, Bacterial; pleuromutiliny; Ribosomes; Pleuromutilins; bakteriální proteiny; linkosamidy; Bacterial Proteins; Streptogramins; elektronová kryomikroskopie; Microbial Sensitivity Tests; Anti-Bacterial Agents; Diterpenes; Polycyclic Compounds; mnohočetná bakteriální léková rezistence; diterpeny; mikrobiální testy citlivosti; Lincosamides; antibakteriální látky; polycyklické sloučeniny; Cryoelectron Microscopy